Dampak Belanja Modal terhadap Cash Holding: Bukti dari Sektor Real Estat dan Properti - Badri, Rico Elhando; Yohanson, A.K. (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2023)
The assessment of a company's financial can be ascertained by examining its cash management practices, particularly in relation to achieving an ideal level of Cash Holding. Existing literature indicates that the level of cash reserves held by a firm can serve as an indicator of the quality of its corporate governance framework. The primary aim of this research is to examine the effect of capital expenditures, net working capital, leverage, and board of commissioners towards the cash holdings of companies operating in the real estate and real estate sector. The research focused on the period spanning from 2019 to 2022. The research used an associative research approach, with a sample size of 31 companies that were selected using purposive selection. The data analysis was used a multiple regression approach, specifically employing panel data. The result of the study shows that net working capital, leverage, and the presence of board of commissioners exert a notable affect the cash holdings, however capital expenditures has no significant effect towards cash holdings. The finding shows that it would be prudent for companies operating in the real estate industry to prioritize the efficient management of net working capital and leverage ratios in order to maintain a robust cash position. Moreover, this underscores the imperative of proactive engagement and supervision by the board of commissioners in the process of making budgetary decisions.